ASSESSMENT OF NATURAL RADIOACTIVITY AND RADIOLOGICAL RISKS IN SOIL OF NUMBUPI MINING SITE IN NIGER STATE, NIGERIA: PUBLIC HEALTH AND ENVIRONMENTAL IMPLICATIONS - Musa, Jibril; Shehu, Abdulsalam; Aregbe, Olubunmi O.; Abubakar, Abdullahi A.; Garba, Nuraddeen N.; Adamu, Usman; Muhammad, Aliyu; Mukhtar, Abdulkadir; Vatsa, Abdullahi M.; Kankara, Usman M.; Yamusa, Yamusa A. (FUDMA JOURNAL OF SCIENCES, 2025)
The study was conducted in Numbupi, a gold-mining settlement in Chanchaga Local Government Area, Niger State, Nigeria. The area features lowland topography surrounded by rock formations and is characterized by open-pit mining practices. The study uses gamma spectrometry with a sodium iodide (NaI (Tl)) detector to assess the natural radioactivity concentrations of Ra, Th, and K in seven soil samples collected from the Numbupi Mining Site in Niger State, Nigeria. The mean activity concentrations of Ra (85.81 18.32 Bq/kg), Th (15.84 8.21 Bq/kg), and K (213.41 89.67 Bq/kg) were calculated and compared with world mean values. A high K concentration in Sample 5 (324.45 Bq/kg) is likely driven by anthropogenic sources, potassium fertilizer application, as it is a well-documented contributor to K enrichment, and natural (alluvial) interactions, while elevated Ra concentration in Samples 1 (136.70 Bq/kg) and 7 (120.72 Bq/kg) correlated with local granitic geology. The following radiological health parameters were calculated: radium equivalent activity (124.90 42.56 Bq/kg), absorbed dose rate (58.11 18.23 nGy/h), annual effective dose equivalent (0.36 0.12 mSv/y), and hazard indices (Hex = 0.34 0.12, Hin = 0.57 0.22). The observed correlations between natural radionuclides (Ra, Th, and K) in the analyzed soil samples reflect complex geological and anthropogenic interactions. The study revealed a strong positive correlation between Th and K (r = +0.85), primarily driven by Samples 5 and 7, indicating that soils with higher thorium concentrations also tend to have elevated potassium levels. All the calculated values were found to be well below international safety...